2021
DOI: 10.7759/cureus.13564
|View full text |Cite
|
Sign up to set email alerts
|

Scientometric Data and Open Access Publication Policies of Clinical Allergy and Immunology Journals

Abstract: Introduction The scientific merit of a paper and its ability to reach broader audiences is essential for scientific impact. Thus, scientific merit measurements are made by scientometric indexes, and journals are increasingly using published papers as open access (OA). In this study, we present the scientometric data for journals published in clinical allergy and immunology and compare the scientometric data of journals in terms of their all-OA and hybrid-OA publication policies. Methods Data were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Similar studies of hematology, and clinical allergy and ımmunology journals conducted previously have reported similar correlations as in the current study. [ 11 12 ] In another study that compared the scientometric indexes of journals in the fields of radiology, nuclear medicine, and medical ımaging, higher correlation coefficients than those of the current study were obtained. [ 20 ] In a study that examined journals in the field of sleep science, the journal found to have the highest JIF value was observed to be a review journal, and JIF was almost twice as high as the next nearest journal.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Similar studies of hematology, and clinical allergy and ımmunology journals conducted previously have reported similar correlations as in the current study. [ 11 12 ] In another study that compared the scientometric indexes of journals in the fields of radiology, nuclear medicine, and medical ımaging, higher correlation coefficients than those of the current study were obtained. [ 20 ] In a study that examined journals in the field of sleep science, the journal found to have the highest JIF value was observed to be a review journal, and JIF was almost twice as high as the next nearest journal.…”
Section: Discussionmentioning
confidence: 62%
“…Studies related to hematology, and clinical allergy and ımmunology journals have shown that despite a strong correlation between different scientometric indexes, as seen in the current study, there was variability in the comparisons of the point rankings of the indexes of these journals. [ 11 12 ] The results obtained in the current study suggest that the comparisons of the scientometric index are directly specific to the scientific branch publishing the journal in question and the structure of the scientometric indexes. According to the results of the present study, the correlation between the SJR and JIF was strong enough to be used interchangeably for ophthalmology journals.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations